2012
DOI: 10.1039/c2ra20147j
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation and N2 adsorption for nanopore determination in silica-polymer composites

Abstract: Silica has two different, fragmented and smooth, visual appearances when deposited onto porous Amberlite polymer substrate from TEOS at acidic and basic pH, respectively. The low temperature N 2 adsorption isotherms on both materials seem to be a combination of Type 1 and Type 4 isotherms with H2 hysteresis, indicating the presence of both micro (D , 2 nm diameter) and meso (2 nm , D , 50 nm) pores. Their mesopore distributions, computed by both BJH and DFT methods, show maxima near Dy5 nm with a narrower pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…The silica gel preparation, used in this experiment was in detail described earlier in references (Halasz et al 2011;Zaleski et al 2012a). The commercially available Amberlite XAD7HP supplied by ROHM and HAAS (now Dow Chemical Co.) was used as a polymer porous template.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The silica gel preparation, used in this experiment was in detail described earlier in references (Halasz et al 2011;Zaleski et al 2012a). The commercially available Amberlite XAD7HP supplied by ROHM and HAAS (now Dow Chemical Co.) was used as a polymer porous template.…”
Section: Methodsmentioning
confidence: 99%
“…This silica material shows non-typical pore structure which results from the applied preparation procedure (Halasz et al 2011;Zaleski et al 2012a). The state of the adsorbate phase during successive stages of pore filling and pore evacuation is deduced from PALS results.…”
Section: Introductionmentioning
confidence: 99%
“…The swelling ratio determined by the volume change before and after adding TEOS for the polymer with naproxen (PNH) equals S% ¼ 80% and differs significantly from those obtained for the pure polymer. The much lower swelling ratio for the composites is the result of the presence of the drug in the sample and the stiffening of the polymer skeleton (Halasz et al, 2011;Kierys et al, 2010;Zaleski et al, 2012).…”
Section: Swelling Experimentsmentioning
confidence: 99%
“…Next, a part of PNH sample was loaded with the silica precursor by wetting the beads with TEOS (1.46 g TEOS/ 1 g of PNH), until all beads were swollen and glassy but did not stick to each other. TEOS is a very effective agent causing the swelling of polymers (Halasz et al, 2011;Kierys et al, 2010;Krasucka et al, 2015;Zaleski et al, 2012). Therefore, it is important for the described preparation procedure to add only so much TEOS, which can be totally entrapped within the pores of the polymer beads.…”
Section: Samples' Preparationmentioning
confidence: 99%
“…Appropriate investigations with composite material characterisation obtained by the polymer swelling strategy on the basis of different polymer matrices (Amberlite XAD7HP and poly(trimethylopropane trimethacrylate)) and precursors of different inorganic phases (tetraethoxysilane and titanium(IV) ethoxide) were made first by Kierys et al [19,20] and Zaleski et al [21,22]. Kierys et al and Zaleski et al demonstrated that composite materials synthesised on the basis of the polymer swelling strategy exhibit interesting porosity which is under the influence of the preparation conditions (especially pH).…”
mentioning
confidence: 99%